2023
DOI: 10.3389/fonc.2023.1071415
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA and hepatocellular carcinoma: A potential therapeutic drug

Abstract: Because of its high prevalence and poor long-term clinical treatment effect, liver disease is regarded as a major public health problem around the world. Among them, viral hepatitis, fatty liver, cirrhosis, non-alcoholic fatty liver disease (NAFLD), and autoimmune liver disease are common causes and inducements of liver injury, and play an important role in the occurrence and development of hepatocellular carcinoma (HCC). Tanshinone IIA (TsIIA) is a fat soluble polyphenol of Salvia miltiorrhiza that is extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 183 publications
(214 reference statements)
0
6
0
Order By: Relevance
“…One critical aspect is the excessive activation of the classical inflammatory signaling pathway NF-kB. The activation of the NF-kB pathway can lead to the secretion of proinflammatory cytokines such as tumor necrosis factorα, interleukin-1 (IL-1), and IL-6, and transforming growth factor-b, which are linked to liver ailments [ 120 ]. These molecular signaling pathways promote the development of MASLD to HCC.…”
Section: Metabolic Shifts and Reprogramming In Masld-induced Hccmentioning
confidence: 99%
“…One critical aspect is the excessive activation of the classical inflammatory signaling pathway NF-kB. The activation of the NF-kB pathway can lead to the secretion of proinflammatory cytokines such as tumor necrosis factorα, interleukin-1 (IL-1), and IL-6, and transforming growth factor-b, which are linked to liver ailments [ 120 ]. These molecular signaling pathways promote the development of MASLD to HCC.…”
Section: Metabolic Shifts and Reprogramming In Masld-induced Hccmentioning
confidence: 99%
“…It has been recently reported that natural products, including phenols, flavonoids, glycosides, quinones, terpenoids, pyrazines, alkaloids, and phenylpropanoids, have antioxidant, energy-producing, anti-inflammatory, anti-apoptotic, and anti-aging effects, which mainly influence the AMPK/Nrf2/mTOR, Nrf2/HO-1, NAMPT/NAD(+)/SIRT, AMPK/SIRT1/PGC-1alpha and PKCs/PARPs/NF-kB signaling pathways, thereby regulating NAD(+) metabolism to prevent and treat NAFLD [ 117 ]. Hepatoprotective effects, caused by the inhibition of PI3K/Akt/mTOR signaling and effective alleviation of oxidative stress damage and ER stress induced by excessive lipid accumulation in hepatocytes, and activation of autophagy were observed for agonists of AMPK thymoquinone [ 118 ] and 5-aminoimidazole-4-carboxamide-1-beta-D-ribofuranoside (AICAR) [ 119 ], agonist of GLP-1/glucagon cotadutide [ 120 ], an antagonist of sphingosine 1-phosphate receptor 2 (S1PR2) JTE-013 [ 26 ], activator of PI3K, autophagy-related genes (ATG) and agonist of Nrf2, PPARα and hemeoxygenase-1 (HO-1) pterostilbene [ 121 ], flavonoid with antioxidant properties involving CYP7A1, quercetin [ 122 ], Pueraria flavonoids [ 92 ], a novel gerotherapy compound, BIOIO-1001 [ 123 ], a natural nonenzymatic antioxidant with low toxicity schisandrin B (Sch B) [ 124 ], H1-antihistamines (AHs) [ 125 ], fat soluble polyphenol Tanshinone IIA (TsIIA) [ 126 ], purendan (PRD) [ 127 ], down-regulating the expression of p-mTOR, p-S6K1 and SREBP-1c, chrysin [ 128 ], red pepper seed extract (RPS) [ 129 ], Gardenia Fructus (GF) extracts [ 130 ], curcumin [ 131 ], and magnesium [ 132 ].…”
Section: New Therapeutic Approaches and Molecular Targets In Nafld/na...mentioning
confidence: 99%
“…For example, TAN-induced HepG2 and Hep3B liver cancer cell apoptosis by activating the caspase-3 and Caspase-8/9 via miR30b-p53-PTPN11/SHP2 signaling pathway, prevented the proliferation of the HepG2 and SMMC-7721 HCC cell lines by downregulating the expression of MMP-2 and MMP-3/9 and blocking NF-κB activation, and inhibited cell invasion and migration by regulating the expression level of E-cadherin and vimentin in HCC cells via TGF-β signaling pathway. 10 TAN inhibited cancer cell-line proliferation by blocking the STAT3 signaling pathway. 3 It is worth noting that the above related signaling pathways have also been confirmed to be closely related to the antioxidant activity and anti-inflammatory response of TAN.…”
Section: Introductionmentioning
confidence: 98%
“…[35][36][37][38][39] For instance, TAN and GA induce cancer cell apoptosis by activating the caspase-3 and Caspase-8/9 via miR30b-p53-PTPN11/SHP2 and MEK-ERK signaling pathways, respectively. 3,10,13 And TAN and GA prevent the proliferation and migration of cancer cells by regulating the expression level of E-cadherin and vimentin in HCC cells via TGF-β and ROS/PKC-α/ERK signaling pathway, respectively. [40][41][42][43] The Results of Process Optimization…”
mentioning
confidence: 99%